Penggunaan Arabizi dalam Konten YouTube: Tinjauan Sosiolinguistik terhadap Proses Alih Bahasa - Ulhaq, Aulia; Fatihin, Muhammad Khairul; As-Sa’idah, Rahmah; Rahma, Vika Faiza; A, Wa Ode Norliza (STIQ Amuntai, 2025)
This study aims to analyze the features of language transfer found in the use of Arabizi on YouTube content, focusing on interference, borrowing, and code mixing. The method used is a qualitative approach through a literature review technique, examining various academic sources and scholarly journals to build a comprehensive analytical framework. The results show that Arabizi, as a writing system of the Arabic language using Latin letters, numbers, and symbols, reflects the complexity of language transfer in three main aspects. First, interference occurs through phonological adaptation, such as the use of numbers to represent Arabic letters that have no equivalent in the Latin alphabet. Second, borrowing is evident in the adoption of linguistic elements from the Latin alphabet and symbols to accommodate technical limitations in digital writing. Third, code mixing appears in the blending of Arabic and English, especially in informal communication on social media. This Arabizi phenomenon reflects how the Arabic language adapts to the demands of modern digital communication while still preserving the cultural identity of its users.